2019
DOI: 10.1186/s12883-019-1456-6
|View full text |Cite
|
Sign up to set email alerts
|

The diffuse involvement of anti-N-methyl-D-aspartate receptor encephalitis in brain: a case report

Abstract: Background Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a severe and most common autoimmune encephalitis in patients under 40 years old. Anti-NMDAR encephalitis has various clinical and neuroimaging findings. Here we report a special case of an anti-NMDAR encephalitis who had diffuse lesions in bilateral hemispheres with mild mass effects in left basal ganglia area. Case presentations A 28-year-old female anti-NMDAR enc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…[20][21][22] Abnormalities may occur in various brain regions and may involve a single site or multiple sites simultaneously. 6,11,13,18,20,[22][23][24] The abnormalities may be unilateral or bilaterally symmetric. 6,11,13,17,18,20,[22][23][24] Dalmau et al reported that 55% of MRI abnormalities were located in the temporal lobe, hippocampus, corpus callosum, cerebral and cerebellar cortex, base of the frontal lobe, basal ganglia, and brainstem.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[20][21][22] Abnormalities may occur in various brain regions and may involve a single site or multiple sites simultaneously. 6,11,13,18,20,[22][23][24] The abnormalities may be unilateral or bilaterally symmetric. 6,11,13,17,18,20,[22][23][24] Dalmau et al reported that 55% of MRI abnormalities were located in the temporal lobe, hippocampus, corpus callosum, cerebral and cerebellar cortex, base of the frontal lobe, basal ganglia, and brainstem.…”
Section: Introductionmentioning
confidence: 99%
“…6,11,13,18,20,[22][23][24] The abnormalities may be unilateral or bilaterally symmetric. 6,11,13,17,18,20,[22][23][24] Dalmau et al reported that 55% of MRI abnormalities were located in the temporal lobe, hippocampus, corpus callosum, cerebral and cerebellar cortex, base of the frontal lobe, basal ganglia, and brainstem. 3,8 A 2015 review conducted by Heine et al reported that 23%-50% of MRI abnormalities were located in the frontal, parietal, and temporal lobes, and that abnormalities were rarely located in the basal ganglia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations